One healthy live birth after preimplantation genetic testing of a cryptic balanced translocation (9;13) in a family with cerebral palsy and glaucoma: a case report - Xiliang Wang; Changsheng Wu; Dongmei Hao; Jinyan Zhang; Chang Tan; De-hua Cheng; Jia Fei; Yuexin Yu (BMC Medical Genomics, 2021)
Abstract Background Cryptic balanced translocations often evade detection by conventional cytogenetics. The preimplantation genetic testing (PGT) technique can be used to help carriers of balanced translocations give birth to healthy offspring; however, for carriers of cryptic balanced translocations, there is only one report about trying assisted reproduction using the PGT technique but with no pregnancy. Case presentation A couple had 3 births out of 4 pregnancies, and all died very young, with two of them having both cerebral palsy and glaucoma. The husband with oligoasthenospermia was found to be a cryptic balanced translocation carrier for t (9,13) (p24.3, q31.3) with G-banding, FISH (fluorescence in-situ hybridization), and MicroSeq techniques; live birth of a healthy baby girl was achieved with PGT/NGS (next-generation sequencing) for the couple. Conclusion Here, we report for the first time a successful live birth of a healthy baby through the PGT technique for a family in which the husband is a carrier of the cryptic balanced translocation t (9,13) (p24.3, q31.3), presumably causative for cerebral palsy and glaucoma. Our study showed that the PGT/NGS technique can effectively help families with a cryptic balanced translocation have healthy offspring.